2000
DOI: 10.1139/b00-069
|View full text |Cite
|
Sign up to set email alerts
|

Preformation, neoformation, and shoot structure in Nothofagus dombeyi (Nothofagaceae)

Abstract: Buds in different positions along trunk, main branch, secondary branch, and short branch parent shoots of young Nothofagus dombeyi (Mirb.) Blume trees were dissected, and the number of organs of their rudimentary shoots was counted. Bud contents were compared with the number of organs of sibling shoots developed in positions equivalent to those of the dissected buds. Cataphyll number was relatively constant for all buds. The number of green leaf primordia differentiated in each bud depended both on the positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 21 publications
7
28
1
1
Order By: Relevance
“…These proventitious buds do not develop into shoots one year after their inception, unlike more distal axillary buds. Some studies have proposed that these proximal buds might form a "bud bank" able to regenerate the branching system after a major damage to their parent shoot [42,44,51]. According to the present study, this would not be the case when damage involves the distal nodes of N. dombeyi shoots, since none of the treatments applied here affected the position of the most proximal branches on shoots.…”
Section: Resilience To Damage Of N Dombeyi Branching Systemscontrasting
confidence: 48%
See 3 more Smart Citations
“…These proventitious buds do not develop into shoots one year after their inception, unlike more distal axillary buds. Some studies have proposed that these proximal buds might form a "bud bank" able to regenerate the branching system after a major damage to their parent shoot [42,44,51]. According to the present study, this would not be the case when damage involves the distal nodes of N. dombeyi shoots, since none of the treatments applied here affected the position of the most proximal branches on shoots.…”
Section: Resilience To Damage Of N Dombeyi Branching Systemscontrasting
confidence: 48%
“…In N. dombeyi trees, like in many other tree species, the branching system consisting of a parent shoot extended in one year and a cohort of offspring shoots extended a year later is characterized by a gradient of increasing offspring shoot size towards the distal end of the parent shoot [42,45,46]. At least for the main branches of young N. dombeyi trees, this gradient seems to be resilient to traumatic factors acting either on the distal portion of a parent shoot before the extension of its offspring shoots (experiments 1 and 2) or on the offspring shoots themselves during their extension (experiment 3).…”
Section: Resilience To Damage Of N Dombeyi Branching Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…by Seino (2001). Puntieri et al (2000) also reported preformed and neoformed shoots in Nothofagus dombei (Mirb.) Blume.…”
Section: Discussionmentioning
confidence: 88%